Evolution of livestock production systems in semi-arid West Africa: Evidence from Niger - Shapiro, Barry I.; Sanders, J.H. (International Livestock Research Institute, 2004)
This paper addresses the problem - with increasing values of land, crops and livestock in the semi-arid region, what happens to the livestock component? The conventional wisdom is that abundant land in more remote areas is more conductive to livestock Development than where human population densities are higher. The paper discusses the anticipated changes in the mixed systems in semi-arid areas, including the evolution of livestock production and the factors driving this process. Then it discusses the contrasting conditions at the two study sites - Libore and Kouka in Niger. A Discrete Stochastic Sequential Programming (DSSP) model is then presented with empirical evidence regarding the potential at the two sites for livestock Development. Further improvements in crop-livestock integration are then discussed as alternative strategies to livestock intensification, as well as the substitutability and complementarity of livestock and crops in these mixed systems. Finally, the conclusions address appropriate policy, the type of research required and Development implications.